Models of tinnitus development. From cochlea to cortex - Krauß, Patrick; Schilling, Achim; Tziridis, Konstantin; Schulze, Holger (HNO, 2019)
The development of subjective tinnitus is still not mechanistically understood and existing models are controversially discussed. In this overview, the authors discuss three of the main models, all of which propose damage to the cochlea as the initial step in tinnitus development. Based on these models, apossible manifestation of tinnitus-related neuronal activity at the perceptually relevant level of the auditory pathway, the auditory cortex, is presented. Furthermore, it is demonstrated that one of the models offers anew view on the phenomenon, which could potentially help patients to better cope with their condition.
CRIS-Team WoS Importer:2019-03-26